Prevention of allergy in infants of allergic mothers by probiotic Escherichia coli - Lodinová-Zádníková, Raja; Prokesová, Ludmila; Kocourková, Ingrid; Hrdý, Jirí; Zizka, Jan (International archives of allergy and immunology, 2010)
BACKGROUND: The objective is to study the effect of after-birth oral colonization by a probiotic Escherichia coli strain in infants of allergic mothers to reduce occurrence of allergy later in life. METHODS: In a controlled clinical trial, 158 infants were randomly divided into groups of (i) 56 colonized infants of allergic mothers, (ii) 57 control infants of allergic mothers, and (iii) 45 control infants of healthy mothers. Incidence rates of bacterial pathogens in stool and levels of anti-E. coli immunoglobulins and some cytokines in serum were determined, and secretory IgA was monitored in stool filtrates and maternal milk. Clinical check-ups of infants aged 4 days, 3 and 6 months, 2, 3 and 5 years were carried out and clinical symptoms of allergy were monitored. One milliliter of the probiotic E. coli strain was administered to infants of allergic mothers at first within 48 h after birth and subsequently 3 times a week over a period of 4 weeks. Control infants of allergic and healthy mothers were monitored in these intervals as well. RESULTS: Presence of the E. coli strain was monitored in stool samples throughout the study. At the conclusion of the study, allergy symptoms were found in 14 infants of control allergic mothers, 7 infants of healthy mothers, and in 2 colonized infants of allergic mothers. Colonization affected levels of several cytokines and specific anti-E. coli antibodies. CONCLUSIONS: After birth, targeted colonization of the intestine by a probiotic E. coli strain can be an effective means of allergy prevention in infants of allergic mothers.
Keywords: alergie; Infant, Newborn; cytokiny; Probiotics; novorozenec; střeva; Adult; Cytokines; Immunoglobulin E; Intestines; lidé; dospělí; Escherichia coli; Hypersensitivity; Humans; imunoglobulin E; probiotika